The impact of agro-food imports from Ukraine on the Romanian market: a post-conflict economic analysis - Ionut Laurentiu PETRE; Robert Ștefan SBÎRCEA; Alina-Oana CHIVA; Cristiana-Adriana COSTACHE (Theoretical and Applied Economics)

(untitled)
The conflict between Russia and Ukraine has had a significant impact on agri-food markets in Eastern Europe, leading to a reconfiguration of trade routes and increased imports from Ukraine. This study analyzes the effects of these changes on the Romanian agri-food market, with a particular focus on price developments. Using a quantitative methodology based on the analysis of data on imports and price fluctuations between the periods 2020-2021 and 2022-2023, the research highlights both the benefits and the challenges generated by these massive imports. The results show that while imports from Ukraine reached a record high in 2022, the impact on prices has been uneven, with prices remaining high despite increased supply. The study emphasizes the importance of support measures for local producers and the need for a balanced strategy to ensure the stability of the Romanian agri-food market.